Do eReferral, eWOM, Familiarity, and Cultural Distance Predict Enrollment Intention among Educational Tourists? Application of Artificial Intelligence Technique - Oday, Akile (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The extant literature has demonstrated the benefits of electronic word-of-mouth (eWOM), electronic referral (eReferral), familiarity, and cultural distance on behavioral outcomes separately. Research efforts have overlooked their collective effects from educational tourism perspective. This dissertation fecundates the concept of eWOM, eReferral, familiarity, and cultural distance with social network theory to explore their influence on enrollment intention. Cross-sectional data garnered from educational tourists based on a judgmental sampling technique were subjected to linear modeling and artificial neural network modeling in training and testing phases. Empirical analysis based on a single-sourced data of n=931 educational tourists confirmed the influence of eReferral, eWOM, familiarity, and cultural distance on enrollment intentions symmetrically (linear modeling) and asymmetrically (artificial neural network). The artificial neural network technique exerted higher predictive relevance and validity. This dissertation provides meaningful theoretical, practical, and methodological insights into the collective and contributive effects of eReferral, eWOM, familiarity, and cultural distance on ed-tourist enrollment intentions. Practically, implications for university administrators and marketers are prescribed. Methodologically, the research provides incremental insights from orthodox (i.e., linear) and contemporary analytical (i.e., artificial neural network) techniques, which are relevant to the wider management and tourism literature. The results suggest that eReferral, eWOM, familiarity and cultural distance can predict intention to enroll in both symmetrically (linear modelling) and asymmetrically (Artificial Neural Network) manner. The asymmetric modeling possesses greater predictive validity and relevance. This study contributes theoretically and methodologically to the management literature by validating the proposed relationships and deploying contemporary method such as Artificial Neural Network.

ÖZ: Mevcut literatür, elektronik ağızdan ağıza iletişim (eWOM), elektronik yönlendirme (eReferral), aşinalık ve kültürel mesafenin davranışsal sonuçlar üzerindeki faydalarını ayrı ayrı göstermiştir. Araştırma çabaları, eğitim turizmi perspektifinden kolektif etkilerini gözden kaçırmıştır. Bu tez, kayıt niyeti üzerindeki etkilerini araştırmak için eWOM, eReferral, aşinalık ve kültürel mesafe kavramlarını sosyal ağ teorisi ile besler. Eğitim turistlerinden yargısal örnekleme tekniğine dayalı olarak elde edilen kesitsel veriler, eğitim ve test aşamalarında doğrusal modelleme ve yapay sinir ağı modellemesine tabi tutulmuştur. n=931 eğitim turistinin tek kaynaklı verilerine dayanan ampirik analiz, eReferral, eWOM, aşinalık ve kültürel mesafenin kayıt niyetleri üzerindeki etkisini simetrik (doğrusal modelleme) ve asimetrik (yapay sinir ağı) olarak doğruladı. Yapay sinir ağı tekniği, daha yüksek öngörücü alaka ve geçerlilik uyguladı. Bu tez, eReferral, eWOM, aşinalık ve kültürel mesafenin ed-turist kayıt niyetleri üzerindeki kolektif ve katkıda bulunan etkilerine dair anlamlı teorik, pratik ve metodolojik içgörüler sağlar. Pratik olarak, üniversite yöneticileri ve pazarlamacılar için çıkarımlar öngörülmüştür. Metodolojik olarak, araştırma, daha geniş yönetim ve turizm literatürü ile ilgili olan ortodoks (yani doğrusal) ve çağdaş analitik (yani yapay sinir ağı) tekniklerinden artan içgörüler sağlar. Sonuçlar, eReferral, eWOM, aşinalık ve kültürel mesafenin hem simetrik (doğrusal modelleme) hem de asimetrik (Yapay Sinir Ağı) şekilde kaydolma niyetini tahmin edebileceğini göstermektedir. Asimetrik modelleme, daha fazla tahmin geçerliliğine ve alaka düzeyine sahiptir. Bu çalışma, önerilen ilişkileri doğrulayarak ve Yapay Sinir Ağı gibi çağdaş bir yöntemi kullanarak yönetim literatürüne teorik ve metodolojik olarak katkıda bulunmaktadır.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Co-Supervisor: Prof. Dr. Mustafa İlkan and Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Thesis Tez; Faculty of Tourism; Tourism--Educational Tourism--Educational Tourist; Foreign Study--International education--Applications--Artificial Intelligence; Students--Travel--Foreign study--Tourism; Familiarity; eReferral; eWOM; Online reviews; Cultural distance; Enrollment; Educational tourism